Kesalahan Morfologi Pada Teks Eksplanasi Siswa SMA Negeri 7 Cirebon - Rina Maulindah; Tati Sri Uswati (Indonesian Language Education and Literature, 2019)
Explanatory texts are new subjects that are important for students to master, including the language system. This study aims to describe the forms of morphological errors in the writing of explanatory essays in class XI students of SMAN 7 Cirebon in the academic year 2019/2020. The subject of this qualitative research was in the form of an explanatory text essay from class XI students of SMA Negeri 7 Cirebon. Data collected through a literature study. Data analysis uses document analysis by identifying, analyzing, and describing morphological errors in explanatory texts written by students. The results of this study indicate that of 58 explanatory texts, there were 296 cases, including 198 or 67% affixation writing errors, 12 or 4% writing reduplication errors and 86 or 29% writing composition/compounding errors.Â Teks eksplanasi merupakan mata pelajaran baru yang penting untuk dikuasai siswa, termasuk sistem kebahasaannya. Penelitian ini bertujuan mendeskripsikan bentuk-bentuk kesalahan morfologi pada penulisan karangan eksplanasi siswa kelas XI SMAN 7 Cirebon tahun pelajaran 2019/2020. Subjek penelitian kualitatif ini berupa karangan teks eksplanasi siswa kelas XI SMA Negeri 7 Cirebon. Data dikumpulkan melalui studi pustaka. Analisis data menggunakan analisis dokumen dengan mengidentifikasi, menganalisis, dan mendeskripsikan kesalahan morfologi pada teks eksplanasi yang ditulis oleh siswa. Hasil penelitian ini menunjukkan bahwa dari 58 teks eksplanasi, terdapat 296 kasus, meliputi: 198 atau 67% kesalahan penulisan afiksasi, 12 atau 4% kesalahan penulisan reduplikasi, dan 86 atau 29% kesalahan penulisan komposisi/pemajemukan.